A gel powder with interpenetrating network structure and its preparation method and application

By using interpenetrating network structure gel powder formed by nanocellulose and polyamic acid in polyurethane coatings, the shortcomings of WPU coatings in mechanical properties and thermal stability are solved, and the mechanical properties and corrosion resistance of the coating are significantly improved.

CN119161600BActive Publication Date: 2025-03-07SUZHOU GANGRUITONG NANO MATERIALS TECH CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411597404.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-03-07
Estimated Expiration
2044-11-11

AI Technical Summary

Technical Problem

The existing water-based polyurethane (WPU) coatings have shortcomings in mechanical properties and thermal stability, and the dispersion and stability of nanocellulose gels in polyurethane coatings are poor.

Method used

A gel powder with an interpenetrating network structure is used. The gel powder is dripped and precipitated under stirring conditions to form an interpenetrating network structure of nanocellulose and polyimide nanofibers.

Benefits of technology

It significantly improves the mechanical properties and corrosion resistance of the polyurethane coating, solves the "soft and weak" defects of nanocellulose gels in mechanical structure, and improves compatibility with the polyurethane matrix.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119161600B_ABST
    Figure CN119161600B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of honeycomb materials, and specifically relates to a gel powder with an interpenetrating network structure, and a preparation method and application thereof. The present invention first prepares a nanocellulose hydrogel solution, and then drips a mixed solution of polyamic acid and polyvinyl pyrrolidone; then undergoes imidization, solvent exchange and freeze drying to obtain a gel powder with an interpenetrating network structure. Under the splitting effect of nanocellulose and the auxiliary effect of polyvinyl pyrrolidone, the polyamic acid mixed solution gradually precipitates to form polyamic acid nanofibers, thereby forming an interpenetrating network structure with nanocellulose. Hydrogen bonds will occur between the nanocellulose in the gel powder and the polyurethane matrix molecules, thereby improving the compatibility of polyimide nanofibers with polyurethane coatings; polyimide nanofibers overcome the defect of "soft and weak" nanocellulose gel materials, and improve the density and mechanical properties of polyurethane coatings.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of honeycomb materials, and in particular relates to a gel powder with an interpenetrating network structure and a preparation method and application thereof. Background Art

[0002] Polyurethane (PU), the full name of which is polyurethane, contains a large number of carbamate structures (-NHCOO-) on the main chain, and is usually synthesized by condensation of isocyanate and polyether or diol polyester. There are many different methods for synthesizing polyurethane, synthetic raw materials and reaction conditions, which makes the structure of each polyurethane very different. Precisely because of the diversity of methods for synthesizing polyurethane, it has a variety of structures. For example, polyurethane synthesized using polyester diol as raw material will have ester bonds, and polyester polyurethane has high strength, good flexibility and UV resistance. Therefore, different synthesis methods make polyurethane carry different functional groups, which can meet the requirements of multiple fields and have a wide range of applications. It has been widely used in industrial fields such as films, coatings, fibers, medicines, adhesives and construction.

[0003] Generally speaking, the synthesis of PU coatings is formed by the polymerization reaction of polyisocyanate monomers and polyol monomers under suitable catalysts and additives. At present, PU has been widely used in industries such as construction, footwear, coal, automobiles, coatings, and biomedicine. It is precisely because of the diversity of raw materials for synthesizing PU coatings that the structure and performance of the formed PU are diversified, which is one of the reasons why PU coatings have a wide range of applications. Polyurethane coatings can be divided into solvent-based polyurethanes and water-based polyurethanes (WPU) according to the different dispersion media. Solvent-based polyurethanes with organic solvents as dispersion media are the most widely used type of polyurethane. WPU, which uses water as a medium and evaporates without solvent, has excellent properties, such as low price, convenient transportation, fast curing speed, good thermal stability, strong adhesion, and high film strength, which makes it widely used in many fields, such as coatings, adhesives, printing inks and other industrial fields. However, in order to ensure the dispersibility of WPU in water, a large number of hydrophilic groups are introduced during the preparation process, which will greatly reduce the water resistance. In addition, the mechanical properties and thermal stability are still lower than those of solvent-based PU coatings. Therefore, in recent years, in order to improve the performance deficiencies of WPU and its functionalization, the research on WPU modification has gradually increased. Common modification methods include cross-linking modification, copolymerization modification, blending modification and composite modification, which has also greatly promoted the rapid development of waterborne polyurethane.

[0004] Blending modification is to physically blend the prepared WPU emulsion with other types of emulsions or some nanomaterials, and evenly disperse them through mechanical stirring or ultrasonic dispersion, so as to prepare the required functional coating. Nanomaterials refer to materials that have at least one dimension in the nanoscale range in three-dimensional space or are composed of them as basic units. Adding nanoparticles to polymers is one of the important methods to improve the performance of polymer materials. At present, there are many nanomaterials used to enhance and improve waterborne polyurethane, mainly including: nanocellulose, nanometal particles, nanocarbon materials, nanooxides, etc. CN118852963A discloses a heat-reflecting heat-insulating coating, in which nano-titanium dioxide is evenly dispersed in a cellulose aerogel matrix and a polyurethane coating, and the aggregation of nano-titanium dioxide is inhibited. The cellulose aerogel improves the flame retardant properties of the coating. CN117801653A discloses a highly elastic hydrophobic radiation-cured wood lacquer skin-feel coating, and the addition of hyperbranched nanocellulose hydrogel realizes the skin-tactile properties of the coating on the wood surface, and the physical and mechanical properties and durability of the coating are improved by reacting the -NH2 group in the hyperbranched nanocellulose hydrogel and the -NCO group in the radiation light-cured coating. CN110105531A and CN107474680A also disclose adding gel materials to the coating to improve the corresponding properties of the coating. However, the above-mentioned technology is only to add modified cellulose gel. As a natural fiber material, the mechanical properties of cellulose gel are relatively low; and cellulose gel has a large specific surface area. Due to the interaction between molecules and the influence of hydrogen bonds, cellulose gel is easily aggregated, so that its dispersibility and stability in polyurethane coatings are poor. At the same time, since the process of preparing cellulose gel is relatively complicated, the cost is high, and the yield is low, it is not suitable for large-scale industrialization. Summary of the invention

[0005] The object of the present invention is to provide a gel powder with an interpenetrating network structure and a preparation method and application thereof. The gel powder prepared by the method has an interpenetrating network structure and improves the mechanical properties of cellulose gel. The gel powder is used to modify polyurethane coatings to form a dense structure on the surface of the polyurethane coating, greatly improving the mechanical properties and anti-corrosion ability of the coating.

[0006] To achieve the above object, the present invention adopts the following technical solution:

[0007] A method for preparing a gel powder having an interpenetrating network structure comprises the following steps:

[0008] (1) treating natural cellulose raw materials to prepare a deionized water dispersion of nanocellulose;

[0009] (2) placing the deionized water dispersion of nanocellulose in an acidic steam bath environment for steam treatment to obtain a nanocellulose hydrogel solution;

[0010] (3) preparing a polyamic acid solution in an organic solvent using diamine and dianhydride as raw materials, then adding polyvinyl pyrrolidone and stirring to obtain a polyamic acid mixed solution; the total weight mass ratio of polyvinyl pyrrolidone to diamine and dianhydride raw materials is (0.01-0.5):1;

[0011] (4) under stirring conditions, adding the polyamic acid mixed solution dropwise to the nanocellulose hydrogel solution; after the addition is completed, adding a chemical imidization reagent; after standing, exchanging with deionized water solvent to obtain a hydrogel with an interpenetrating network structure;

[0012] (5) The hydrogel with an interpenetrating network structure is freeze-dried and crushed to obtain a gel powder with an interpenetrating network structure.

[0013] Cellulose is a common high molecular polymer in nature, widely found in plants such as cotton, hemp and wood, and has the advantages of good biocompatibility, renewability, biodegradability, environmental friendliness and non-toxicity. Nanocellulose is made from cellulose, and has at least one dimensional space size of less than 100nm. Nanocellulose composite hydrogel materials not only retain the unique physical and chemical properties of cellulose, such as hydrophilicity, biocompatibility, biodegradability, high chemical activity and dimensional stability, but also have new structural characteristics given by micro-nano processing technology, such as light weight, softness, high specific surface area, high crystallinity, high strength, high modulus and mild chemical activity. Because the surface of cellulose nanofibers has abundant hydroxyl groups, cellulose exhibits high hydrophilicity, and can quickly form a uniform and stable nanocellulose suspension in the coating, which is widely used.

[0014] However, nanocellulose has low mechanical properties and has limited performance improvement on the coating. In addition, due to its large specific surface area and strong hydrogen bonding, nanocellulose is prone to agglomeration, and has poor compatibility with the matrix and uneven dispersion. In previous works (CN118667223A, CN118812911A, CN118702962A, etc.), the inventors first prepared hydrogels and then directly added fibrous fillers or water-soluble polyamic acid salts. In this method, the fibrous fillers can only be dispersed outside the hydrogel and cannot penetrate into the gel to form an interpenetrating structure. The water-soluble polyamic acid salts cannot be precipitated into fibrous structures.

[0015] In order to solve the problems existing in nanocellulose, the present invention first prepares nanocellulose gel, and then prepares polymer nanofibers through a precipitation process. The precipitation method is a common process for preparing polymer nanofibers in the prior art, but directly pouring polyamic acid into the precipitation liquid will obtain micron or even millimeter-sized fibers, and nanometer-sized fiber structures cannot be prepared.

[0016] The present invention drips the polyamic acid mixed solution into the nanocellulose hydrogel solution under stirring. Among them, the nanocellulose not only plays a role in forming an interpenetrating network structure; more importantly, under the state of rapid stirring, the nanocellulose fibers in the solution can play a "sickle"-like splitting role, so that the polyamic acid mixed solution is split into bundles with smaller diameters, thereby reducing the diameter of the polyamic acid fibers. In order to further make the fiber diameter reach the nanometer level, and also to enable the polyamic acid solution to form a stable bundle structure in the rapidly stirred nanocellulose hydrogel solution, the generation of the nanofiber structure is promoted. The present invention adds a certain amount of polyvinyl pyrrolidone. On the one hand, the polyvinyl pyrrolidone molecule contains a pyridine ring structure, which can form a hydrogen bond with the imine structure and carboxyl group on the polyamic acid, provide an adsorption force, and enable the organic solution "bundle" of the polyamic acid to be stably dispersed in the nanocellulose hydrogel solution; on the other hand, the polyvinyl pyrrolidone also has a hydrophilic effect, and can hydrate with the water molecules in the nanocellulose hydrogel solution. When the polyamic acid mixed solution is added dropwise to the nanocellulose hydrogel solution, the adsorption force and hydration force of polyvinyl pyrrolidone cause polyvinyl pyrrolidone to be dispersed in the outer surface of the "tow" of the organic solution of polyamic acid. Since polyvinyl pyrrolidone itself has a high viscosity, it can promote the stability of the "tow" structure. Under the shear force provided by stirring and the "cutting" effect of nanocellulose, the "tow" can gradually become longer and thinner, thereby increasing the aspect ratio of the polyimide fiber and promoting the formation of the nanofiber structure. The molecular weight of polyvinyl pyrrolidone is not particularly limited, and its specific number average molecular weight can be 8000-200000.

[0017] In general, under the splitting effect of nanocellulose and the auxiliary effect of polyvinyl pyrrolidone, the polyamic acid mixed solution can form fine liquid flows in the stirred nanocellulose hydrogel solution and gradually precipitate to form polyamic acid nanofibers, thereby forming an interpenetrating network structure with nanocellulose.

[0018] This composite functional gel material not only retains the original properties of the gel material, but also combines the high modulus, high strength, thermal stability, high chemical activity and other properties of nanocellulose and polyimide nanofibers with the solution properties of hydrogels, making up for the "soft and weak" defects of nanocellulose gel materials in mechanical structure, and laying the foundation for potential application development of gels.

[0019] Furthermore, in step (1), the natural cellulose raw material is at least one of cotton, bamboo powder, waste paper, flax, sisal, straw, and bagasse.

[0020] Furthermore, the treatment method in step (1) includes at least one of high pressure homogenization, acid hydrolysis, enzymatic hydrolysis, and TEMPO oxidation. Furthermore, the nanocellulose of the present invention is prepared by TEMPO oxidation. The full name of TEMPO is 2,2,6,6-tetramethylpiperidinyl oxide, which is an organic nitrogen oxide with weak oxidizing properties. This method has a short reaction time, is non-toxic, and has a low cost, and the morphology and size of the prepared nanocellulose are relatively uniform.

[0021] Furthermore, in step (1), the diameter of the nanocellulose is 10-100 nm and the length is 5-20 μm. By controlling the process parameters of the TEMPO oxidation method, the aspect ratio of the nanocellulose can be effectively adjusted and the degree of interaction between the nanocellulose and the polyimide nanofiber can be improved.

[0022] Furthermore, in step (2), the acidic vapor bath is at least one of a formic acid vapor bath, an acetic acid vapor bath, a hydrochloric acid vapor bath, and a nitric acid vapor bath; and the vapor bath treatment time is 2-10 hours.

[0023] Furthermore, in step (3), the total weight mass ratio of nanocellulose to diamine and dianhydride raw materials is (0.5-2):1; further, the total weight mass ratio of nanocellulose to diamine and dianhydride raw materials is (1-1.5):1. The types of diamine and dianhydride are not particularly limited, and the molar ratio of dianhydride monomer to diamine monomer is 1:(0.95-1.05); the organic solvent used in the reaction is at least one of N-methylpyrrolidone, dimethylformamide, and dimethylacetamide. Specifically, the dianhydride monomer is at least one of pyromellitic acid dianhydride, 3,3',4,4'-biphenyl tetracarboxylic acid dianhydride, 3,3',4,4'-diphenyl ether tetracarboxylic acid dianhydride, hexafluoro dianhydride, and 3,3',4,4'-benzophenone tetracarboxylic acid dianhydride; the diamine monomer is at least one of 4,4'-diaminodiphenyl ether, 4,4'-diaminodiphenylmethane, and p-phenylenediamine.

[0024] Furthermore, in step (4), the stirring rate is 400-800 rpm; the chemical imidization agent is a mixture of acetic anhydride and pyridine in a molar ratio of (1-3):1, and the mass of the mixture is 10-30% of the mass of the polyamic acid solution. Furthermore, in step (4), the stirring rate is 600-700 rpm. An appropriate stirring rate can avoid the reduction of the aspect ratio of the polyimide nanofibers due to too fast stirring rate, and can also prevent the defect of a thicker diameter due to too slow stirring rate.

[0025] On the other hand, the present invention also provides an application of the gel powder having an interpenetrating network structure, and the gel powder having an interpenetrating network structure is used in the field of polyurethane coatings.

[0026] The polyurethane coating comprises the following components in parts by weight: 100 parts of aqueous polyurethane dispersion; and 0.5-5 parts of the gel powder having an interpenetrating network structure.

[0027] The large number of hydroxyl groups on the surface of nanocellulose in the gel powder will form hydrogen bonds with the polyurethane matrix molecules, enhancing the interfacial interaction between the gel powder and the polyurethane matrix, solving the technical problem of poor compatibility between polyimide nanofibers and polyurethane coatings. Polyimide nanofibers have high mechanical properties, solving the "soft and weak" defect of nanocellulose gel materials in mechanical structure. Nanocellulose and polyimide nanofibers form an interpenetrating structure, allowing the two to be fully entangled, exerting a synergistic reinforcement effect, and improving the density and mechanical properties of the polyurethane coating.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] (1) The production process of the present invention is simple, easy to operate, highly efficient, and industrially scalable.

[0030] (2) First, prepare nanocellulose hydrogel and construct nanocellulose-based gel material, and then drop the polyamic acid mixed solution into the nanocellulose hydrogel solution under stirring. Under the splitting effect of nanocellulose and the auxiliary effect of polyvinyl pyrrolidone, the polyamic acid mixed solution can form fine liquid flows in the stirred nanocellulose hydrogel solution and gradually precipitate to form polyamic acid nanofibers, thereby forming an interpenetrating network structure with nanocellulose.

[0031] (3) Hydrogen bonds will occur between the nanocellulose in the gel powder and the polyurethane matrix molecules, solving the technical problem of poor compatibility between polyimide nanofibers and polyurethane coatings. Polyimide nanofibers solve the "soft and weak" defect of nanocellulose gel materials in mechanical structure. Nanocellulose and polyimide nanofibers form an interpenetrating structure, and the two play a synergistic role in improving the density and mechanical properties of the polyurethane coating. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is a scanning electron microscope image of the gel powder prepared in Example 10;

[0033] Figure 2 This is a scanning electron microscope image of the gel powder prepared in Comparative Example 1. DETAILED DESCRIPTION

[0034] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0035] Example 1

[0036] A method for preparing a gel powder having an interpenetrating network structure comprises the following steps:

[0037] (1) Processing natural cellulose raw materials to prepare a deionized water dispersion of nanocellulose; the nanocellulose is prepared from bamboo powder by TEMPO oxidation method; the diameter of the nanocellulose is 80 nm and the length is 10 μm;

[0038] (2) placing the deionized water dispersion of nanocellulose in an acidic steam bath environment for steam treatment to obtain a nanocellulose hydrogel solution; the acidic steam bath is a formic acid steam bath; and the steam bath treatment time is 4 hours;

[0039] (3) A polyamic acid solution is prepared in an organic solvent using diamine and dianhydride as raw materials, and then polyvinyl pyrrolidone is added and stirred to obtain a polyamic acid mixed solution; the number average molecular weight of polyvinyl pyrrolidone is 30,000; the total weight mass ratio of polyvinyl pyrrolidone to diamine and dianhydride raw materials is 0.01:1; the total weight mass ratio of nanocellulose to diamine and dianhydride raw materials is 1.5:1; the molar ratio of dianhydride monomer to diamine monomer is 1:0.95; the organic solvent used in the reaction is N-methylpyrrolidone; the dianhydride monomer is pyromellitic dianhydride; and the diamine monomer is 4,4'-diaminodiphenyl ether;

[0040] (4) under stirring conditions, adding the polyamic acid mixed solution dropwise to the nanocellulose hydrogel solution; after the addition is completed, adding a chemical imidization agent; after standing, exchanging with deionized water solvent to obtain a hydrogel with an interpenetrating network structure; the stirring rate is 600 rpm; the chemical imidization agent is a mixture of acetic anhydride and pyridine in a molar ratio of 1:1, and the mass of the mixture is 15% of the mass of the polyamic acid solution;

[0041] (5) The hydrogel with an interpenetrating network structure is freeze-dried and crushed to obtain a gel powder with an interpenetrating network structure.

[0042] A polyurethane coating comprises the following components in parts by weight: 100 parts of aqueous polyurethane dispersion and 4 parts of gel powder with an interpenetrating network structure.

[0043] Example 2

[0044] A method for preparing a gel powder having an interpenetrating network structure comprises the following steps:

[0045] (1) Processing natural cellulose raw materials to prepare a deionized water dispersion of nanocellulose; the nanocellulose is prepared from bamboo powder by TEMPO oxidation method; the diameter of the nanocellulose is 80 nm and the length is 10 μm;

[0046] (2) placing the deionized water dispersion of nanocellulose in an acidic steam bath environment for steam treatment to obtain a nanocellulose hydrogel solution; the acidic steam bath is an acetic acid steam bath; and the steam bath treatment time is 8 hours;

[0047] (3) A polyamic acid solution is prepared in an organic solvent using diamine and dianhydride as raw materials, and then polyvinyl pyrrolidone is added and stirred to obtain a polyamic acid mixed solution; the number average molecular weight of polyvinyl pyrrolidone is 30,000; the total weight mass ratio of polyvinyl pyrrolidone to diamine and dianhydride raw materials is 0.5:1; the total weight mass ratio of nanocellulose to diamine and dianhydride raw materials is 1:1; the molar ratio of dianhydride monomer to diamine monomer is 1:1.03; the organic solvent used in the reaction is dimethylformamide; the dianhydride monomer is 3,3',4,4'-biphenyltetracarboxylic dianhydride; and the diamine monomer is 4,4'-diaminodiphenylmethane;

[0048] (4) under stirring conditions, adding the polyamic acid mixed solution dropwise to the nanocellulose hydrogel solution; after the addition is completed, adding a chemical imidization agent; after standing, exchanging with deionized water solvent to obtain a hydrogel with an interpenetrating network structure; the stirring rate is 700 rpm; the chemical imidization agent is a mixture of acetic anhydride and pyridine in a molar ratio of 2:1, and the mass of the mixture is 25% of the mass of the polyamic acid solution;

[0049] (5) The hydrogel with an interpenetrating network structure is freeze-dried and crushed to obtain a gel powder with an interpenetrating network structure.

[0050] A polyurethane coating comprises the following components in parts by weight: 100 parts of aqueous polyurethane dispersion and 3 parts of gel powder with an interpenetrating network structure.

[0051] Example 3

[0052] A method for preparing a gel powder having an interpenetrating network structure comprises the following steps:

[0053] (1) Processing natural cellulose raw materials to prepare a deionized water dispersion of nanocellulose; the nanocellulose is prepared from bamboo powder by TEMPO oxidation method; the diameter of the nanocellulose is 80 nm and the length is 10 μm;

[0054] (2) placing the deionized water dispersion of nanocellulose in an acidic steam bath environment for steam treatment to obtain a nanocellulose hydrogel solution; the acidic steam bath is a hydrochloric acid steam bath; and the steam bath treatment time is 5 hours;

[0055] (3) A polyamic acid solution is prepared in an organic solvent using diamine and dianhydride as raw materials, and then polyvinyl pyrrolidone is added and stirred to obtain a polyamic acid mixed solution; the number average molecular weight of polyvinyl pyrrolidone is 30,000; the total weight mass ratio of polyvinyl pyrrolidone to diamine and dianhydride raw materials is 0.01:1; the total weight mass ratio of nanocellulose to diamine and dianhydride raw materials is 1.5:1; the molar ratio of dianhydride monomer to diamine monomer is 1:1; the organic solvent used in the reaction is dimethylacetamide; the dianhydride monomer is 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride; and the diamine monomer is 4,4'-diaminodiphenylmethane;

[0056] (4) under stirring conditions, adding the polyamic acid mixed solution dropwise to the nanocellulose hydrogel solution; after the addition is completed, adding a chemical imidization agent; after standing, exchanging with deionized water solvent to obtain a hydrogel with an interpenetrating network structure; the stirring rate is 700 rpm; the chemical imidization agent is a mixture of acetic anhydride and pyridine in a molar ratio of 2.5:1, and the mass of the mixture is 20% of the mass of the polyamic acid solution;

[0057] (5) The hydrogel with an interpenetrating network structure is freeze-dried and crushed to obtain a gel powder with an interpenetrating network structure.

[0058] A polyurethane coating comprises the following components in parts by weight: 100 parts of aqueous polyurethane dispersion and 4 parts of gel powder with an interpenetrating network structure.

[0059] Example 4

[0060] A method for preparing a gel powder having an interpenetrating network structure comprises the following steps:

[0061] (1) Processing natural cellulose raw materials to prepare a deionized water dispersion of nanocellulose; the nanocellulose is prepared from bamboo powder by TEMPO oxidation method; the diameter of the nanocellulose is 80 nm and the length is 10 μm;

[0062] (2) placing the deionized water dispersion of nanocellulose in an acidic steam bath environment for steam treatment to obtain a nanocellulose hydrogel solution; the acidic steam bath is an acetic acid steam bath; and the steam bath treatment time is 5 hours;

[0063] (3) A polyamic acid solution is prepared in an organic solvent using diamine and dianhydride as raw materials, and then polyvinyl pyrrolidone is added and stirred to obtain a polyamic acid mixed solution; the number average molecular weight of polyvinyl pyrrolidone is 30,000; the total weight mass ratio of polyvinyl pyrrolidone to diamine and dianhydride raw materials is 0.1:1; the total weight mass ratio of nanocellulose to diamine and dianhydride raw materials is 1.1:1; the molar ratio of dianhydride monomer to diamine monomer is 1:0.98; the organic solvent used in the reaction is N-methylpyrrolidone; the dianhydride monomer is 3,3',4,4'-biphenyltetracarboxylic dianhydride; the diamine monomer is a mixture of 4,4'-diaminodiphenyl ether and 4,4'-diaminodiphenylmethane in a molar ratio of 1:1;

[0064] (4) under stirring conditions, adding the polyamic acid mixed solution dropwise to the nanocellulose hydrogel solution; after the addition is completed, adding a chemical imidization agent; after standing, exchanging with deionized water solvent to obtain a hydrogel with an interpenetrating network structure; the stirring rate is 620 rpm; the chemical imidization agent is a mixture of acetic anhydride and pyridine in a molar ratio of 1.5:1, and the mass of the mixture is 18% of the mass of the polyamic acid solution;

[0065] (5) The hydrogel with an interpenetrating network structure is freeze-dried and crushed to obtain a gel powder with an interpenetrating network structure.

[0066] A polyurethane coating comprises the following components in parts by weight: 100 parts of aqueous polyurethane dispersion and 3 parts of gel powder with an interpenetrating network structure.

[0067] Example 5

[0068] A method for preparing a gel powder having an interpenetrating network structure comprises the following steps:

[0069] (1) Processing natural cellulose raw materials to prepare a deionized water dispersion of nanocellulose; the nanocellulose is prepared from bamboo powder by TEMPO oxidation method; the diameter of the nanocellulose is 80 nm and the length is 10 μm;

[0070] (2) placing the deionized water dispersion of nanocellulose in an acidic steam bath environment for steam treatment to obtain a nanocellulose hydrogel solution; the acidic steam bath is an acetic acid steam bath; and the steam bath treatment time is 7 hours;

[0071] (3) A polyamic acid solution is prepared in an organic solvent using diamine and dianhydride as raw materials, and then polyvinyl pyrrolidone is added and stirred to obtain a polyamic acid mixed solution; the number average molecular weight of polyvinyl pyrrolidone is 30,000; the total weight mass ratio of polyvinyl pyrrolidone to diamine and dianhydride raw materials is 0.3:1; the total weight mass ratio of nanocellulose to diamine and dianhydride raw materials is 1.4:1; the molar ratio of dianhydride monomer to diamine monomer is 1:1.03; the organic solvent used in the reaction is dimethylformamide; the dianhydride monomer is 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride; and the diamine monomer is 4,4'-diaminodiphenyl ether;

[0072] (4) under stirring conditions, adding the polyamic acid mixed solution dropwise to the nanocellulose hydrogel solution; after the addition is completed, adding a chemical imidization agent; after standing, exchanging with deionized water solvent to obtain a hydrogel with an interpenetrating network structure; the stirring rate is 680 rpm; the chemical imidization agent is a mixture of acetic anhydride and pyridine in a molar ratio of 2.5:1, and the mass of the mixture is 24% of the mass of the polyamic acid solution;

[0073] (5) The hydrogel with an interpenetrating network structure is freeze-dried and crushed to obtain a gel powder with an interpenetrating network structure.

[0074] A polyurethane coating comprises the following components in parts by weight: 100 parts of aqueous polyurethane dispersion and 3 parts of gel powder with an interpenetrating network structure.

[0075] Example 6

[0076] A method for preparing a gel powder having an interpenetrating network structure comprises the following steps:

[0077] (1) Processing natural cellulose raw materials to prepare a deionized water dispersion of nanocellulose; the nanocellulose is prepared from bamboo powder by TEMPO oxidation method; the diameter of the nanocellulose is 80 nm and the length is 10 μm;

[0078] (2) placing the deionized water dispersion of nanocellulose in an acidic steam bath environment for steam treatment to obtain a nanocellulose hydrogel solution; the acidic steam bath is an acetic acid steam bath; and the steam bath treatment time is 6 hours;

[0079] (3) A polyamic acid solution is prepared in an organic solvent using diamine and dianhydride as raw materials, and then polyvinyl pyrrolidone is added and stirred to obtain a polyamic acid mixed solution; the number average molecular weight of polyvinyl pyrrolidone is 30,000; the total weight mass ratio of polyvinyl pyrrolidone to diamine and dianhydride raw materials is 0.3:1; the total weight mass ratio of nanocellulose to diamine and dianhydride raw materials is 0.5:1; the molar ratio of dianhydride monomer to diamine monomer is 1:1.01; the organic solvent used in the reaction is dimethylacetamide; the dianhydride monomer is a mixture of pyromellitic dianhydride and 3,3',4,4'-biphenyltetracarboxylic dianhydride in a molar ratio of 3:1; the diamine monomer is a mixture of 4,4'-diaminodiphenyl ether and 4,4'-diaminodiphenylmethane in a molar ratio of 1:1;

[0080] (4) under stirring conditions, adding the polyamic acid mixed solution dropwise to the nanocellulose hydrogel solution; after the addition is completed, adding a chemical imidization agent; after standing, exchanging with deionized water solvent to obtain a hydrogel with an interpenetrating network structure; the stirring rate is 650 rpm; the chemical imidization agent is a mixture of acetic anhydride and pyridine in a molar ratio of 2:1, and the mass of the mixture is 20% of the mass of the polyamic acid solution;

[0081] (5) The hydrogel with an interpenetrating network structure is freeze-dried and crushed to obtain a gel powder with an interpenetrating network structure.

[0082] A polyurethane coating comprises the following components in parts by weight: 100 parts of aqueous polyurethane dispersion and 3 parts of gel powder with an interpenetrating network structure.

[0083] Example 7

[0084] A method for preparing a gel powder having an interpenetrating network structure comprises the following steps:

[0085] (1) Processing natural cellulose raw materials to prepare a deionized water dispersion of nanocellulose; the nanocellulose is prepared from bamboo powder by TEMPO oxidation method; the diameter of the nanocellulose is 80 nm and the length is 10 μm;

[0086] (2) placing the deionized water dispersion of nanocellulose in an acidic steam bath environment for steam treatment to obtain a nanocellulose hydrogel solution; the acidic steam bath is an acetic acid steam bath; and the steam bath treatment time is 6 hours;

[0087] (3) A polyamic acid solution is prepared in an organic solvent using diamine and dianhydride as raw materials, and then polyvinyl pyrrolidone is added and stirred to obtain a polyamic acid mixed solution; the number average molecular weight of polyvinyl pyrrolidone is 30,000; the total weight mass ratio of polyvinyl pyrrolidone to diamine and dianhydride raw materials is 0.3:1; the total weight mass ratio of nanocellulose to diamine and dianhydride raw materials is 2:1; the molar ratio of dianhydride monomer to diamine monomer is 1:1.01; the organic solvent used in the reaction is dimethylacetamide; the dianhydride monomer is a mixture of pyromellitic dianhydride and 3,3',4,4'-biphenyltetracarboxylic dianhydride in a molar ratio of 3:1; the diamine monomer is a mixture of 4,4'-diaminodiphenyl ether and 4,4'-diaminodiphenylmethane in a molar ratio of 1:1;

[0088] (4) under stirring conditions, adding the polyamic acid mixed solution dropwise to the nanocellulose hydrogel solution; after the addition is completed, adding a chemical imidization agent; after standing, exchanging with deionized water solvent to obtain a hydrogel with an interpenetrating network structure; the stirring rate is 650 rpm; the chemical imidization agent is a mixture of acetic anhydride and pyridine in a molar ratio of 2:1, and the mass of the mixture is 20% of the mass of the polyamic acid solution;

[0089] (5) The hydrogel with an interpenetrating network structure is freeze-dried and crushed to obtain a gel powder with an interpenetrating network structure.

[0090] A polyurethane coating comprises the following components in parts by weight: 100 parts of aqueous polyurethane dispersion and 3 parts of gel powder with an interpenetrating network structure.

[0091] Example 8

[0092] A method for preparing a gel powder having an interpenetrating network structure comprises the following steps:

[0093] (1) Processing natural cellulose raw materials to prepare a deionized water dispersion of nanocellulose; the nanocellulose is prepared from bamboo powder by TEMPO oxidation method; the diameter of the nanocellulose is 80 nm and the length is 10 μm;

[0094] (2) placing the deionized water dispersion of nanocellulose in an acidic steam bath environment for steam treatment to obtain a nanocellulose hydrogel solution; the acidic steam bath is an acetic acid steam bath; and the steam bath treatment time is 6 hours;

[0095] (3) A polyamic acid solution is prepared in an organic solvent using diamine and dianhydride as raw materials, and then polyvinyl pyrrolidone is added and stirred to obtain a polyamic acid mixed solution; the number average molecular weight of polyvinyl pyrrolidone is 30,000; the total weight mass ratio of polyvinyl pyrrolidone to diamine and dianhydride raw materials is 0.3:1; the total weight mass ratio of nanocellulose to diamine and dianhydride raw materials is 1.2:1; the molar ratio of dianhydride monomer to diamine monomer is 1:1.01; the organic solvent used in the reaction is dimethylacetamide; the dianhydride monomer is a mixture of pyromellitic dianhydride and 3,3',4,4'-biphenyltetracarboxylic dianhydride in a molar ratio of 3:1; the diamine monomer is a mixture of 4,4'-diaminodiphenyl ether and 4,4'-diaminodiphenylmethane in a molar ratio of 1:1;

[0096] (4) under stirring conditions, adding the polyamic acid mixed solution dropwise to the nanocellulose hydrogel solution; after the addition is completed, adding a chemical imidization agent; after standing, exchanging with deionized water solvent to obtain a hydrogel with an interpenetrating network structure; the stirring rate is 400 rpm; the chemical imidization agent is a mixture of acetic anhydride and pyridine in a molar ratio of 2:1, and the mass of the mixture is 20% of the mass of the polyamic acid solution;

[0097] (5) The hydrogel with an interpenetrating network structure is freeze-dried and crushed to obtain a gel powder with an interpenetrating network structure.

[0098] A polyurethane coating comprises the following components in parts by weight: 100 parts of aqueous polyurethane dispersion and 3 parts of gel powder with an interpenetrating network structure.

[0099] Example 9

[0100] A method for preparing a gel powder having an interpenetrating network structure comprises the following steps:

[0101] (1) Processing natural cellulose raw materials to prepare a deionized water dispersion of nanocellulose; the nanocellulose is prepared from bamboo powder by TEMPO oxidation method; the diameter of the nanocellulose is 80 nm and the length is 10 μm;

[0102] (2) placing the deionized water dispersion of nanocellulose in an acidic steam bath environment for steam treatment to obtain a nanocellulose hydrogel solution; the acidic steam bath is an acetic acid steam bath; and the steam bath treatment time is 6 hours;

[0103] (3) A polyamic acid solution is prepared in an organic solvent using diamine and dianhydride as raw materials, and then polyvinyl pyrrolidone is added and stirred to obtain a polyamic acid mixed solution; the number average molecular weight of polyvinyl pyrrolidone is 30,000; the total weight mass ratio of polyvinyl pyrrolidone to diamine and dianhydride raw materials is 0.3:1; the total weight mass ratio of nanocellulose to diamine and dianhydride raw materials is 1.2:1; the molar ratio of dianhydride monomer to diamine monomer is 1:1.01; the organic solvent used in the reaction is dimethylacetamide; the dianhydride monomer is a mixture of pyromellitic dianhydride and 3,3',4,4'-biphenyltetracarboxylic dianhydride in a molar ratio of 3:1; the diamine monomer is a mixture of 4,4'-diaminodiphenyl ether and 4,4'-diaminodiphenylmethane in a molar ratio of 1:1;

[0104] (4) under stirring conditions, adding the polyamic acid mixed solution dropwise to the nanocellulose hydrogel solution; after the addition is completed, adding a chemical imidization agent; after standing, exchanging with deionized water solvent to obtain a hydrogel with an interpenetrating network structure; the stirring rate is 800 rpm; the chemical imidization agent is a mixture of acetic anhydride and pyridine in a molar ratio of 2:1, and the mass of the mixture is 20% of the mass of the polyamic acid solution;

[0105] (5) The hydrogel with an interpenetrating network structure is freeze-dried and crushed to obtain a gel powder with an interpenetrating network structure.

[0106] A polyurethane coating comprises the following components in parts by weight: 100 parts of aqueous polyurethane dispersion and 3 parts of gel powder with an interpenetrating network structure.

[0107] Example 10

[0108] A method for preparing a gel powder having an interpenetrating network structure comprises the following steps:

[0109] (1) Processing natural cellulose raw materials to prepare a deionized water dispersion of nanocellulose; the nanocellulose is prepared from bamboo powder by TEMPO oxidation method; the diameter of the nanocellulose is 80 nm and the length is 10 μm;

[0110] (2) placing the deionized water dispersion of nanocellulose in an acidic steam bath environment for steam treatment to obtain a nanocellulose hydrogel solution; the acidic steam bath is an acetic acid steam bath; and the steam bath treatment time is 6 hours;

[0111] (3) A polyamic acid solution is prepared in an organic solvent using diamine and dianhydride as raw materials, and then polyvinyl pyrrolidone is added and stirred to obtain a polyamic acid mixed solution; the number average molecular weight of polyvinyl pyrrolidone is 30,000; the total weight mass ratio of polyvinyl pyrrolidone to diamine and dianhydride raw materials is 0.3:1; the total weight mass ratio of nanocellulose to diamine and dianhydride raw materials is 1.2:1; the molar ratio of dianhydride monomer to diamine monomer is 1:1.01; the organic solvent used in the reaction is dimethylacetamide; the dianhydride monomer is a mixture of pyromellitic dianhydride and 3,3',4,4'-biphenyltetracarboxylic dianhydride in a molar ratio of 3:1; the diamine monomer is a mixture of 4,4'-diaminodiphenyl ether and 4,4'-diaminodiphenylmethane in a molar ratio of 1:1;

[0112] (4) under stirring conditions, adding the polyamic acid mixed solution dropwise to the nanocellulose hydrogel solution; after the addition is completed, adding a chemical imidization agent; after standing, exchanging with deionized water solvent to obtain a hydrogel with an interpenetrating network structure; the stirring rate is 650 rpm; the chemical imidization agent is a mixture of acetic anhydride and pyridine in a molar ratio of 2:1, and the mass of the mixture is 20% of the mass of the polyamic acid solution;

[0113] (5) The hydrogel with an interpenetrating network structure is freeze-dried and crushed to obtain a gel powder with an interpenetrating network structure.

[0114] A polyurethane coating comprises the following components in parts by weight: 100 parts of aqueous polyurethane dispersion and 3 parts of gel powder with an interpenetrating network structure.

[0115] Comparative Example 1

[0116] A method for preparing a gel powder having an interpenetrating network structure comprises the following steps:

[0117] (1) Processing natural cellulose raw materials to prepare a deionized water dispersion of nanocellulose; the nanocellulose is prepared from bamboo powder by TEMPO oxidation method; the diameter of the nanocellulose is 80 nm and the length is 10 μm;

[0118] (2) A polyamic acid solution is prepared in an organic solvent using diamine and dianhydride as raw materials, and then polyvinyl pyrrolidone is added and stirred to obtain a polyamic acid mixed solution; the number average molecular weight of polyvinyl pyrrolidone is 30,000; the total weight mass ratio of polyvinyl pyrrolidone to diamine and dianhydride raw materials is 0.3:1; the total weight mass ratio of nanocellulose to diamine and dianhydride raw materials is 1.2:1; the molar ratio of dianhydride monomer to diamine monomer is 1:1.01; the organic solvent used in the reaction is dimethylacetamide; the dianhydride monomer is a mixture of pyromellitic dianhydride and 3,3',4,4'-biphenyltetracarboxylic dianhydride in a molar ratio of 3:1; the diamine monomer is a mixture of 4,4'-diaminodiphenyl ether and 4,4'-diaminodiphenylmethane in a molar ratio of 1:1;

[0119] (3) under stirring conditions, the polyamic acid mixed solution is added dropwise to the deionized water dispersion of nanocellulose; after the addition is completed, a chemical imidization agent is added; the stirring rate is 650 rpm; the chemical imidization agent is a mixture of acetic anhydride and pyridine in a molar ratio of 2:1, and the mass of the mixture is 20% of the mass of the polyamic acid solution;

[0120] (4) placing the mixed dispersion after the dropwise addition in an acidic steam bath environment for steam treatment, and then exchanging with deionized water solvent to obtain a hydrogel with an interpenetrating network structure; the acidic steam bath is an acetic acid steam bath; and the steam bath treatment time is 6 hours;

[0121] (5) The hydrogel with an interpenetrating network structure is freeze-dried and crushed to obtain a gel powder with an interpenetrating network structure.

[0122] A polyurethane coating comprises the following components in parts by weight: 100 parts of aqueous polyurethane dispersion and 3 parts of gel powder with an interpenetrating network structure.

[0123] Comparative Example 2

[0124] A method for preparing a gel powder having an interpenetrating network structure comprises the following steps:

[0125] (1) The natural cellulose raw material is treated, and then nanocellulose and polyvinyl pyrrolidone are mixed and stirred evenly to prepare a deionized water dispersion of nanocellulose; the nanocellulose is prepared from bamboo powder by TEMPO oxidation method; the diameter of the nanocellulose is 80nm and the length is 10μm; the number average molecular weight of polyvinyl pyrrolidone is 30000; the total weight mass ratio of polyvinyl pyrrolidone to diamine and dianhydride raw materials is 0.3:1;

[0126] (2) placing the deionized water dispersion of nanocellulose in an acidic steam bath environment for steam treatment to obtain a nanocellulose hydrogel solution; the acidic steam bath is an acetic acid steam bath; and the steam bath treatment time is 6 hours;

[0127] (3) A polyamic acid mixed solution is prepared in an organic solvent using diamine and dianhydride as raw materials; the total weight mass ratio of nanocellulose to diamine and dianhydride raw materials is 1.2:1; the molar ratio of dianhydride monomer to diamine monomer is 1:1.01; the organic solvent used in the reaction is dimethylacetamide; the dianhydride monomer is a mixture of pyromellitic dianhydride and 3,3',4,4'-biphenyltetracarboxylic dianhydride in a molar ratio of 3:1; the diamine monomer is a mixture of 4,4'-diaminodiphenyl ether and 4,4'-diaminodiphenylmethane in a molar ratio of 1:1;

[0128] (4) under stirring conditions, adding the polyamic acid mixed solution dropwise to the nanocellulose hydrogel solution; after the addition is completed, adding a chemical imidization agent; after standing, exchanging with deionized water solvent to obtain a hydrogel with an interpenetrating network structure; the stirring rate is 650 rpm; the chemical imidization agent is a mixture of acetic anhydride and pyridine in a molar ratio of 2:1, and the mass of the mixture is 20% of the mass of the polyamic acid solution;

[0129] (5) The hydrogel with an interpenetrating network structure is freeze-dried and crushed to obtain a gel powder with an interpenetrating network structure.

[0130] A polyurethane coating comprises the following components in parts by weight: 100 parts of aqueous polyurethane dispersion and 3 parts of gel powder with an interpenetrating network structure.

[0131] Comparative Example 3

[0132] A method for preparing a gel powder having an interpenetrating network structure comprises the following steps:

[0133] (1) Processing natural cellulose raw materials to prepare a deionized water dispersion of nanocellulose; the nanocellulose is prepared from bamboo powder by TEMPO oxidation method; the diameter of the nanocellulose is 80 nm and the length is 10 μm;

[0134] (2) placing the deionized water dispersion of nanocellulose in an acidic steam bath environment for steam treatment to obtain a nanocellulose hydrogel solution; the acidic steam bath is an acetic acid steam bath; and the steam bath treatment time is 6 hours;

[0135] (3) A polyamic acid solution is prepared in an organic solvent using diamine and dianhydride as raw materials, and then polyvinyl pyrrolidone is added and stirred to obtain a polyamic acid mixed solution; the number average molecular weight of polyvinyl pyrrolidone is 30,000; the total weight mass ratio of polyvinyl pyrrolidone to diamine and dianhydride raw materials is 1:1; the total weight mass ratio of nanocellulose to diamine and dianhydride raw materials is 1.2:1; the molar ratio of dianhydride monomer to diamine monomer is 1:1.01; the organic solvent used in the reaction is dimethylacetamide; the dianhydride monomer is a mixture of pyromellitic dianhydride and 3,3',4,4'-biphenyltetracarboxylic dianhydride in a molar ratio of 3:1; the diamine monomer is a mixture of 4,4'-diaminodiphenyl ether and 4,4'-diaminodiphenylmethane in a molar ratio of 1:1;

[0136] (4) under stirring conditions, adding the polyamic acid mixed solution dropwise to the nanocellulose hydrogel solution; after the addition is completed, adding a chemical imidization agent; after standing, exchanging with deionized water solvent to obtain a hydrogel with an interpenetrating network structure; the stirring rate is 650 rpm; the chemical imidization agent is a mixture of acetic anhydride and pyridine in a molar ratio of 2:1, and the mass of the mixture is 20% of the mass of the polyamic acid solution;

[0137] (5) The hydrogel with an interpenetrating network structure is freeze-dried and crushed to obtain a gel powder with an interpenetrating network structure.

[0138] A polyurethane coating comprises the following components in parts by weight: 100 parts of aqueous polyurethane dispersion and 3 parts of gel powder with an interpenetrating network structure.

[0139] Performance test: The polyurethane coatings prepared in Examples 1-10 and Comparative Examples 1-3 were subjected to hardness test (GB / T6739-2006), paint film adhesion test (GB / T 5210-2006) and salt spray resistance test (GB / T1771-2007); the test results are shown in Table 1.

[0140]

[0141] Figure 1 and Figure 2 The following are scanning electron microscope images of the gel powder prepared in Example 10 and Comparative Example 1. Figure 1 It can be seen that the rough surface of polyimide nanofibers and nanocellulose form an interlaced structure, indicating that under the splitting effect of nanocellulose and the auxiliary effect of polyvinyl pyrrolidone, the polyamic acid mixed solution can form a fine liquid flow in the stirred nanocellulose hydrogel solution, and gradually precipitate to form polyamic acid nanofibers, thereby forming an interpenetrating network structure with nanocellulose. Figure 2It can be seen that comparative example 1 does not form a gel network of nanocellulose in advance. When the polyamic acid mixed solution is directly added dropwise to the deionized water dispersion of nanocellulose, the randomly distributed nanocellulose cannot play a similar "sickle" splitting effect, but moves with stirring like polyamic acid, causing polyamic acid to be directly precipitated on the surface of nanocellulose, and agglomerate to form a large amount of lamellar structures. At the same time, comparative examples 2-3 show that polyvinyl pyrrolidone needs to be added to the polyamic acid solution in advance. If it is added to the nanocellulose aqueous dispersion in advance, due to the presence of abundant hydroxyl groups on the surface of nanocellulose, it will form a stronger hydrogen bond with polyvinyl pyrrolidone, and it is impossible to attach to the surface of the polyamic acid subsequently added dropwise, and the organic solution "tow" of polyamic acid cannot be stably dispersed in the nanocellulose hydrogel solution, affecting the formation of polymer nanofibers. Comparative example 3 shows that attention should be paid to the amount of polyvinyl pyrrolidone. Due to the large viscosity of polyvinyl pyrrolidone, when its amount is too much, it will affect the dispersion of polyamic acid in the nanocellulose hydrogel solution, which is not conducive to the formation of an interpenetrating network.

[0142] The embodiments described in the present invention are merely descriptions of the preferred implementation modes of the present invention, and are not intended to limit the concept and scope of the present invention. Without departing from the design concept of the present invention, various modifications and improvements made to the technical solutions of the present invention by engineers and technicians in this field should fall within the protection scope of the present invention. The technical contents for which protection is sought in the present invention have all been recorded in the claims.

Claims

1. A method for preparing a gel powder having an interpenetrating network structure, characterized in that: The following steps are involved: (1) treating natural cellulose raw materials to prepare a deionized water dispersion of nanocellulose; (2) placing the deionized water dispersion of nanocellulose in an acidic steam bath environment for steam treatment to obtain a nanocellulose hydrogel solution; (3) preparing a polyamic acid solution in an organic solvent using diamine and dianhydride as raw materials, then adding polyvinyl pyrrolidone and stirring to obtain a polyamic acid mixed solution; the total weight mass ratio of polyvinyl pyrrolidone to diamine and dianhydride raw materials is (0.01-0.5):1; (4) under stirring conditions, adding the polyamic acid mixed solution dropwise into the nanocellulose hydrogel solution; After the dropwise addition is completed, a chemical imidization reagent is added; after standing, the solution is exchanged with a deionized water solvent to obtain a hydrogel having an interpenetrating network structure; (5) The hydrogel with an interpenetrating network structure is freeze-dried and crushed to obtain a gel powder with an interpenetrating network structure.

2. The method for preparing a gel powder having an interpenetrating network structure according to claim 1, characterized in that: In step (1), the natural cellulose raw material is at least one of cotton, bamboo powder, waste paper, flax, sisal, straw and bagasse.

3. The method for preparing a gel powder having an interpenetrating network structure according to claim 1, characterized in that: The treatment method in step (1) includes at least one of high pressure homogenization, acid hydrolysis, enzymatic hydrolysis, and TEMPO oxidation.

4. The method for preparing a gel powder having an interpenetrating network structure according to claim 1, characterized in that: In step (1), the diameter of the nanocellulose is 10-100 nm and the length is 5-20 μm.

5. The method for preparing a gel powder having an interpenetrating network structure according to claim 1, characterized in that: In step (2), the acidic steam bath is at least one of a formic acid steam bath, an acetic acid steam bath, a hydrochloric acid steam bath, and a nitric acid steam bath; and the steam bath treatment time is 2-10 hours.

6. The method for preparing a gel powder having an interpenetrating network structure according to claim 1, characterized in that: In step (3), the total weight mass ratio of nanocellulose to diamine and dianhydride raw materials is (0.5-2):

1.

7. The method for preparing a gel powder having an interpenetrating network structure according to claim 1, characterized in that: In step (4), the stirring rate is 400-800 rpm; the chemical imidization reagent is a mixture of acetic anhydride and pyridine in a molar ratio of (1-3):1, and the mass of the mixture is 10-30% of the mass of the polyamic acid solution.

8. A gel powder having an interpenetrating network structure, characterized in that: The gel powder is prepared by the method for preparing a gel powder having an interpenetrating network structure as described in any one of claims 1 to 7.

9. An application of a gel powder having an interpenetrating network structure as claimed in claim 8, characterized in that: The gel powder with interpenetrating network structure is used in the field of polyurethane coatings.

10. A polyurethane coating, characterized in that: Contains the following components in parts by weight: 100 parts of aqueous polyurethane dispersion; 0.5-5 parts of the gel powder with interpenetrating network structure as claimed in claim 8.

Citation Information

Patent Citations

  • Environment-friendly antibacterial waterborne wood coating

    CN107474680A

  • Preparation method of antibacterial coating used for paper

    CN110105531A

  • Preparation method of high-elastic hydrophobic radiation curing wood paint skin feeling coating

    CN117801653A

  • Modified aerogel powder as well as preparation method and application thereof

    CN118667223A

  • Polyimide graphene gel powder as well as preparation method and application thereof

    CN118702962A